2010
DOI: 10.1155/2010/176514
|View full text |Cite
|
Sign up to set email alerts
|

Keratouveitis as a First Presentation of Relapsing Polychondritis

Abstract: This paper provides images and a description of an unusual manifestation of relapsing polychondritis presenting initially with isolated ocular signs, mimicking infective keratitis. We present an interventional case report of a 75-year-old man who presented with marked left ocular irritation and photophobia. Ophthalmological examination disclosed corneal intrastromal infiltrate and hypopyon which failed to respond to intensive antimicrobial drops. He later went on to develop bilateral auricular chondritis. Rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Another series found that 8.2% of the patients with scleritis-associated uveitis had RP (14). Typically, nongranulomatous anterior uveitis is seen (15), often in conjunction with scleritis. Cyclitic membranes have been reported (16); however, hypopyon uveitis without scleritis is very exceptional (17).…”
Section: Discussionmentioning
confidence: 99%
“…Another series found that 8.2% of the patients with scleritis-associated uveitis had RP (14). Typically, nongranulomatous anterior uveitis is seen (15), often in conjunction with scleritis. Cyclitic membranes have been reported (16); however, hypopyon uveitis without scleritis is very exceptional (17).…”
Section: Discussionmentioning
confidence: 99%
“…Relapsing polychondritis mainly affects cartilaginous tissues and collagen-rich tissues. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 Eyeballs are collagen-rich organs that are unavoidable sites of inflammation in patients with relapsing polychondritis, with the affected areas including the conjunctiva, sclera, cornea, uvea, retina, and optic nerve. Therefore, conjunctivitis, episcleritis or scleritis, keratitis, uveitis, and retinopathy are very common ocular manifestations in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Relapsing polychondritis is an unusual multiorgan autoimmune disease characterized by recurrent inflammation and progressive destruction of cartilaginous structures and collagen-rich tissues, including the eyes, ears, nose, skin, renal, musculoskeletal, heart, and respiratory systems. 1 , 2 , 3 , 4 , 5 , 6 , 7 Ocular manifestations, including proptosis, eyelid edema, conjunctivitis, episcleritis, keratitis, uveitis, secondary open glaucoma, and retinopathy often occur in more than half of patients with relapsing polychondritis. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 We experienced the case of a patient with relapsing polychondritis who presented with ocular complications, including conjunctivitis, episcleritis, keratouveitis, secondary angle closure glaucoma, and complicated cataract.…”
Section: Introductionmentioning
confidence: 99%
“…RP most commonly presents as auricular chondritis and polyarthritis, which occur in over 80% of patients, 31 but RP can affect almost every organ system ( Table 2). Constitutional symptoms include fever, fatigue, weight loss, night sweats, and enlarged inguinal lymph nodes.…”
Section: Systemic Diseasementioning
confidence: 99%
“…3,28 Corneal infiltrates in RP, sometimes associated with a hypopyon, can mimic infectious keratitis. 10,31 Uvea According to Letko, uveitis occurs in about 25% of RP patients and is usually anterior uveitis or sclerouveitis. 28 Hypopyon uveitis may occur as a presenting feature of RP.…”
Section: Corneamentioning
confidence: 99%